LVL-concrete composite floor systems: an effective solution for multi-storey timber buildings - Yeoh, David (2008)
Timber-concrete composite (TCC) floor systems utilize composite action between a timber joist and a concrete topping to increase their span. Their overall structural performance is significantly influenced by the load-slip relationship, strength, stiffness and positions of the connectors providing the composite action. The relatively low elastic modulus of timber, however, may affect the dynamic (vibration) performance of medium to long-span TCC floors. Three broad areas are currently under investigation at the University of Canterbury: (1) the choice of the best type of connection: (2) the collapse behaviour under static (gravity) loads; and (3) the vibration susceptibility. This paper presents preliminary results of experimental tests used to characterise the connection systems as they are tested to failure under monotonic loads. Based on those outcomes, a semi-prefabricated composite floor system is proposed. The system is constructed from prefabricated panels made from timber joists and plywood sheets, and by a concrete slab cast-in-situ on top of the panels. Two different types of connection systems are shown to perform satisfactorily: notches cut from laminated veneer lumber (LVL) joists and reinforced with coach screws, and toothed metal plates pressed into LVL joists. Finally, an overview of the extensive experimental programme currently ongoing is provided.